2014
DOI: 10.14260/jemds/2014/2041
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Stress and Autonomic Function Test in Medical Students

Abstract: BACKGROUND: Medical students are frequently described as stressed in comparison with general population. 1,2 Particularly examinations are a major cause of stress. 3 High level of stress may have adverse effect on academic achievement. However there is a deficit of information regarding the interrelationship of stress and academic performance in medical students. The present study adds to the literature of the level of stress during examination and its impact on performance in a cohort of first year medical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 12 publications
0
45
0
Order By: Relevance
“…From the diffraction curve of TiO 2 nanoparticles synthesized in the same condition as ET5, it can be found that the peaks were very sharp and the strong peaks at 2θ = 25.3° corresponded to the (101) crystal plane of anatase phase of TiO 2 . And also other crystal planes such as, (004), (200), (211), (204) corresponded to the standard diffraction patterns of face‐centered tetragonal anatase titanium dioxide (JPCDS NO.21‐1272),43–45 which confirmed successful formation of pure anatase phase in given solvothermal reaction condition. According to the calculation of Scherrer equation using the (101) peak, the average crystalline size of the anatase phase TiO 2 was around 4 nm.…”
Section: Resultsmentioning
confidence: 61%
“…From the diffraction curve of TiO 2 nanoparticles synthesized in the same condition as ET5, it can be found that the peaks were very sharp and the strong peaks at 2θ = 25.3° corresponded to the (101) crystal plane of anatase phase of TiO 2 . And also other crystal planes such as, (004), (200), (211), (204) corresponded to the standard diffraction patterns of face‐centered tetragonal anatase titanium dioxide (JPCDS NO.21‐1272),43–45 which confirmed successful formation of pure anatase phase in given solvothermal reaction condition. According to the calculation of Scherrer equation using the (101) peak, the average crystalline size of the anatase phase TiO 2 was around 4 nm.…”
Section: Resultsmentioning
confidence: 61%
“…A number of deposition methods have been used to prepare doped titania films such as sputtering , chemical solution deposition , pulsed laser deposition and sol–gel method . For practical applications sol–gel method is widely used because it provides numerous advantages over other fabrication techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Photocatalysis has been shown to be an attractive alternative, and using TiO 2 particles in suspension has achieved promising results. [32][33][34] The metal ions present in effluents are usually found complexed by substances such as EDTA or Cyanide, species widely used in industrial applications. The photocatalytic treatment of these solutions has shown several problems where the oxidation of the EDTA is achieved, the reduction of metal ions is not attained; 30 or when cyanide complexes are present.…”
Section: Photo-assisted Electrolytic Copper Ions Removalmentioning
confidence: 99%
“…29 Although the results obtained with particulate materials have shown that the heterogeneous photocatalysis is a promising alternative of remediation for this type of effluent, findings have also revealed disadvantages related with the separation, recovery and recycling of the catalyst and metallic deposits from the treated effluents. [29][30][31][32][33][34] An alternative and effective methodology to overcome these inconveniences is photoassisted electrolysis. 35 With this technique, the TiO 2 is supported on a conductive substrate to be used as the anode and coupled with a conductive material acting as a cathode.…”
Section: Photo-assisted Electrolytic Copper Ions Removalmentioning
confidence: 99%